Formaldehyde-Free Wood Composite Fabricated Using Oil Palm Starch Modified with Glutardialdehyde as the Binder - Mohd Hazim Mohamad Amini; Rokiah Hashim; Nurul Syuhada Sulaiman (International Journal of Chemical Engineering)
Oil palm trunk is a kind of biomass rich in starch content. Oil palm trunk waste was available throughout the year in Malaysia and Indonesia due to continuous felling of nonproductive, over 25-year-old trees. Even though some manufacturers were using it in plywood and veneer production, they are hard to handle which later becomes less favorable raw materials due to a high moisture content where combination with a high starch content quickly attracts fungus and wood-decaying agents. The objective of this work was to evaluate properties of experimental wood composite panels, manufactured using oil palm-extracted starch modified with glutardialdehyde (OPSMG) as a binder. Different analyses were employed to characterize the properties of the samples besides evaluation of bending, internal bonding strength, and dimensional stability of the panels. Characterization on the functional group using the FT-IR analysis showed presence of aldehyde groups and ketone stretching vibrations at 1736.05 cm−1 and 1596.25 cm−1, which proves the presence of glutardialdehyde besides formation of bonding between the OPSMG and the woody materials. The XRD analysis showed the starch modification had lowered the crystallinity index which in turn increased the strength of the manufactured wood composites. The OPSMG wood composites were also found to have lower thermal stability, as evaluated using the TGA analysis. It was recorded that the maximum modulus of rupture for OPSMG wood composites was achieved at the 0.80 g/cm3 density level with an average value of 15.446 N/mm2 which showed 38.00% increment in strength between those two types of wood composites. Thickness swelling after immersion in water can still be improved by incorporating the moisture-repellent material later. After analyzing the results, it was concluded that modified oil palm starch has the potential to be used as an environment friendly binder for wood composite making.